IMPORTANCE OF THE ASSESMENT OF GAMMA GLUTAMYL TRANSFERASE IN TYPE 2 DIABETES MELLITUS - SANJEEDA TABASUM.M (International Journal of Pharma and Bio Sciences, 2013)
To evaluate the importance of Gamma Glutamyltansferase in type 2 Diabetic population for the diagnostic role via oxidative stress. Materials & Methods: A total of 302 subjects were included in case control study, consisting of 198 diabetic and 104 controls that were sex and age matched. Serum total cholesterol, triglyceride and HDL Cholesterol were measured using Siemens kits and GGT was measured using Avecon kit on Chem 200 analyser. Results & Discussions: Patients were gender matched with p-value .273. Sugar parameters with significant results of p value 0.001** and the mean value of FBS being 169.09±82.44 mg/dL, PPBS mean value is 267.17±102.75 mg/dL compared to control group. Lipid parameters have shown total cholesterol mean of diabetic group 294.94±110.48 mg/dL and 202.36±50.48 mg/dL with the p value 0.001** and triglyceride mean being 273.77±148.27 mg/dL, control mean 112.05±39.16 mg/dL with the p value 0.001**. HDL: LDL has also shown significant value of p 0.001**. SGOT mean of diabetic group127.22 ±10.26 U/L and normal control 25.23±U/L and SGPT mean of diabetic group 30.29±11.22U/L and control mean 26.65±7.5U/L the p-value 0.003**.Gamma glutamyltransferase significant levels of the liver enzyme in diabetic population mean 46.63±15.41U/L showing significance of p=<0.001**